2021
DOI: 10.1002/jcph.2000
|View full text |Cite
|
Sign up to set email alerts
|

Physiologically Based Pharmacokinetic Modeling and Dose Adjustment of Teicoplanin in Pediatric Patients With Renal Impairment

Abstract: The pharmacokinetics of teicoplanin differs in children as compared with adults, and especially in renally impaired pediatric patients. Inappropriate empirical antibacterial therapy may lead to treatment-related antibacterial resistance and increased toxicity, making adjustment of the dosage regimen essential. In the present study, physiologically based pharmacokinetic (PBPK) models were developed to define the appropriate dosage regimen for pediatric patients with differing renal function. Our PBPK models acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Verified PBPK models of drugs are presented in support of pediatric dose prediction (Figure 4 ): 13 articles reported results from P‐PBPK models, which are presented in support of dose selection, 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 five articles were on the optimization of dosage in the design of future pediatric clinical studies, 3 , 29 , 43 , 44 , 45 and six articles reported findings from studies on determining dose regimens. 46 , 47 , 48 , 49 , 50 , 51 Fourteen publications were on some special pediatric populations and uncommon diseases with an assessment of renal impairment, 52 , 53 , 54 , 55 , 56 children with obesity, 57 , 58 , 59 , 60 and pediatric patients with severe coronavirus disease 2019 (COVID‐19) disease. 61 , 62 , 63 , 64 , 65 Consistent with this trend, several big research funding/grants for computational pharmaceutics worldwide were launched (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Verified PBPK models of drugs are presented in support of pediatric dose prediction (Figure 4 ): 13 articles reported results from P‐PBPK models, which are presented in support of dose selection, 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 five articles were on the optimization of dosage in the design of future pediatric clinical studies, 3 , 29 , 43 , 44 , 45 and six articles reported findings from studies on determining dose regimens. 46 , 47 , 48 , 49 , 50 , 51 Fourteen publications were on some special pediatric populations and uncommon diseases with an assessment of renal impairment, 52 , 53 , 54 , 55 , 56 children with obesity, 57 , 58 , 59 , 60 and pediatric patients with severe coronavirus disease 2019 (COVID‐19) disease. 61 , 62 , 63 , 64 , 65 Consistent with this trend, several big research funding/grants for computational pharmaceutics worldwide were launched (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we demonstrated that PBPK modelling might be a useful tool to predict the PK of compounds that are renally cleared in paediatric subjects with CKD. Other studies have successfully used PBPK modelling to simulate PK of renally excreted drugs in paediatric CKD populations by solely reducing the GFR of the virtual population, as compounds included in these studies did not undergo tubular secretion like 3TC and FTC [ 37 , 38 , 39 , 40 ]. Ye et al applied PBPK modelling to predict PK of ertapenem in paediatric CKD populations, considering both glomerular filtration and tubular secretion [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…A scenario in which altered PK is expected can necessitate a dose adjustment. With PBPK modeling, it is not only possible to study the effect of age on drug PK, an additional effect of, for example, co-medication, ethnicity, renal impairment or obesity on a drug's PK profile can also be investigated [25][26][27].…”
Section: Physiologically Based Pharmacokinetic (Pbpk) Modelingmentioning
confidence: 99%